OPTIMIZING THE VIRTUAL LEARNING ENVIRONMENT THROUGH PROMPTING STRATEGIES TO REDUCE STUDENTS' COGNITIVE LOAD IN BIOGRAPHY TEXT LEARNING - Suwadji; Abdur Rofik; Imron Rosyadi Hamid; Siti Saidatus Salamah; Nisaul Barokati Seliro Wangi (Universitas Islam Raden Rahmat Malang, 2026)
The rapid adoption of Virtual Learning Environments (VLE) in literacy instruction presents both opportunities and challenges, particularly concerning the cognitive load imposed on students when comprehending complex narrative texts such as biographies. This study investigates the effectiveness of both process-oriented and content-oriented prompting strategies within a VLE in reducing students' cognitive load during biographical text instruction. Drawing upon Cognitive Load Theory (CLT) and Mayer's seven principles of multimedia learning, this study employed a quasi-experimental design involving 65 secondary school students, who were randomly assigned to either an experimental group (utilizing a VLE with reinforced prompting) or a control group (utilizing a conventional VLE). The findings reveal that students in the prompting-enhanced VLE class demonstrated significantly lower extrinsic cognitive load and higher germane cognitive load compared to the control group. Process-oriented prompts effectively mitigated extraneous cognitive processing, whereas content-related prompts enhanced learner motivation and facilitated deeper engagement with the biographical texts. These results affirm that well-designed prompts within a VLE play a pivotal role in literacy instruction, offering practical pedagogical implications for educators seeking to balance the affordances of technology with students' cognitive constraints.